Mesenchymal stem cell therapy for non-healing diabetic foot ulcer infection: New insight - Mahmoudvand, Golnaz; Karimi Rouzbahani, Arian; Razavi, Zahra Sadat; Mahjoor, Mohamad; Afkhami, Hamed (Frontiers in Bioengineering and Biotechnology, 2023)
Diabetic foot ulcer (DFU) is considered the most catastrophic complication of diabetes mellitus (DM), leading to repeated hospitalizations, infection, gangrene, and finally amputation of the limb. In patients suffering from DM, the wound-healing process is impaired due to various factors such as endothelial dysfunction and synthesis of advanced glycation end-products, hence, conventional therapeutic interventions might not be effective. With increasing therapeutic applications of mesenchymal stem cells (MSCs) in recent years, their potential as a method for improving the wound-healing process has gained remarkable attention. In this field, MSCs exert their beneficial effects through immunomodulation, differentiation into the essential cells at the site of ulcers, and promoting angiogenesis, among others. In this article, we review cellular and molecular pathways through which MSC therapy reinforces the healing process in non-healing DFUs.